Public Responsibility Towards Indonesian Idol's Music Talent: An Adorno Perspective - Budiawan, Hery; Torondek, Timothy Revival April; Nyarong, Wise Witness; Koswara, Jason (Resital: Jurnal Seni Pertunjukan, 2024)
The music expressed around us, particularly in the realm of competitive music, faces significant challenges in maintaining subjectivity and objectivity to ensure a fair competition process. This study examines reality shows like Indonesian Idol, questioning whether they are pure competitions or avenues for capitalist profit. From Adorno's perspective, this issue is linked to societal impact, highlighting three main problems: standardization, commodification, and massification. Using both quantitative and qualitative methods, this research involved 67 respondents who completed questionnaires to explore the systematic flaws in Indonesian Idol’s competition structure. The study aimed to analyse how these flaws align with Adorno's concepts of standardization, commodification, and massification, and their influence on public perception and critical thinking. The quantitative aspect involved statistical analysis of questionnaire responses, while the qualitative approach included in-depth interviews to gain insights into participants' views on transparency and fairness in the competition. The findings indicate that Indonesian Idol’s competition system is heavily influenced by industry standards that prioritize commercial success over artistic integrity. This results in a homogenized musical output that caters to mass appeal, undermining the authenticity of the competition. Additionally, the commodification of contestants transforms them into marketable products rather than genuine artists, while the massification process dilutes the cultural significance of the musical content presented. The study concludes that for reality shows to serve as responsible public entertainment, they must instil transparency and fairness in their competition processes. Implementing these principles can foster a more critical and discerning audience, ensuring that such shows contribute positively to the cultural landscape rather than merely serving commercial interests